O uso das estratégias de leitura para compreensão textual pelos alunos da Educação de Jovens e Adultos (EJA) - Büchler, Adriana Alves (2009)
This Work aims at investigating reading strategies used by Commerce Social Service Institution (CSSI-SESC) Education for Young People and Adults (EYPA-EJA) pupils, in Casa Amarela neighborhood, Recife, Pernambuco in order to verify the way their utilizations- i.e. Reading strategies ones- have interfered on the texts comprehension skills, abilities. One has appraised every pupil comprehension level , as well as their understanding impressions regarding to the text, so to say, their textual comprehensibleness. In this perspective, this diagnostic points out the reading most steadfast strategies, since every pupil/reader applies his own criteria when he/she constructs a certain meaning for his/her reading. Ten pupils have participated in this Research. Five ones among them came from II Basic Teaching and other five ones stemmed from High School Teaching. The pupils have made the text reading aiming at verifying the strategies they use in order to understand them, i. e. the texts. Through this way, one could perceive, still, the reading strategies (selection, anticipation, inference and verification), employed by the pupils during their activities in this regard. The demands imposed on account of the success achievement in society comprise having skills, abilities, necessary to read and understand different textual genders, since this understanding interferes directly in their personal and professional development. This Research has contributed to teaching practice reflection, fundamentation and understanding, since it has shown up that the pupils specific (subjective) reading strategies for texts understanding have always as principal support the same ones universe, with their previous and constant, steadfast experiences inherent to textual context. In addition to this one, one has ascertained that understanding nonexistence any affirmation regarding to pupils/readers is precipitated, hastened since this Research participants have shown up, demonstrated this characteristic presence, which was denominated as Textual Comprehensibleness. In, through the made individual analyses, some evidences have arisen from this particularity. In short, on the whole, this Research has revealed, pointed out that the reading strategies, adopted, taken on the reading act are indispensable for the texts comprehensive knowledge. One has considered,acknowledged, therefore, that in the reading mechanism, put into practice by pupils, there have been registers, records that have been appointed up as (Textual Comprehensibleness), important point in the reading context, since, in the reading act and in the texts understanding, comprehension, it must be included the existential contexts and the acquired experiences by the pupils/readers.